GLANDULAR TRICHOME IN THE ASTERACEAE FAMILY - Wina Dyah Puspita Sari; Cicik Suriani; Dina Handayani (BIOLINK (Jurnal Biologi Lingkungan Industri Kesehatan), 2021)
The Asteraceae is a diverse plant species and widely distributed, especially in the tropics and subtropics, consisting of 1,600 - 1,700 genera which include 24,000 - 30,000  species. Asteraceae has characteristics of cup flowers and brackets that are not owned by other plants. The objective of this study was to determine the morphological structure of plants and escpecially the leaf glandular trichome in several species of Asteraceae. The research method used was a descriptive method, to describe and interpret the shape, structure and distribution of leaf trichome in the Asteraceae family. This study used eight species of the Asteraceae family, namely Elephantopus mollis, Bidens pilosa, Tithonia deversifolia, Tridax procumbens, Synedrella nodiflora, Eclipta prostrate, Sphagneticola trilobata and Ageratum conyzoides. The observation results of trichomes at 8 species by Scanning Electrone Microscope (SEM) was obtained varied forms of trichomes, both in shape and size. From the research, it was obtained that the forms of multicellular glandular trichome with various shapes, ranging in size from 50.6 µm - 831.9 µm.